If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 14(3 + -2x) + 7 = 4 + -1x + 5(2 + -3x) 14x + (3 * 14 + -2x * 14) + 7 = 4 + -1x + 5(2 + -3x) 14x + (42 + -28x) + 7 = 4 + -1x + 5(2 + -3x) Reorder the terms: 42 + 7 + 14x + -28x = 4 + -1x + 5(2 + -3x) Combine like terms: 42 + 7 = 49 49 + 14x + -28x = 4 + -1x + 5(2 + -3x) Combine like terms: 14x + -28x = -14x 49 + -14x = 4 + -1x + 5(2 + -3x) 49 + -14x = 4 + -1x + (2 * 5 + -3x * 5) 49 + -14x = 4 + -1x + (10 + -15x) Reorder the terms: 49 + -14x = 4 + 10 + -1x + -15x Combine like terms: 4 + 10 = 14 49 + -14x = 14 + -1x + -15x Combine like terms: -1x + -15x = -16x 49 + -14x = 14 + -16x Solving 49 + -14x = 14 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 49 + -14x + 16x = 14 + -16x + 16x Combine like terms: -14x + 16x = 2x 49 + 2x = 14 + -16x + 16x Combine like terms: -16x + 16x = 0 49 + 2x = 14 + 0 49 + 2x = 14 Add '-49' to each side of the equation. 49 + -49 + 2x = 14 + -49 Combine like terms: 49 + -49 = 0 0 + 2x = 14 + -49 2x = 14 + -49 Combine like terms: 14 + -49 = -35 2x = -35 Divide each side by '2'. x = -17.5 Simplifying x = -17.5
| 14x=y-4 | | (3v-2)(3-v)=0 | | z/16=-28 | | z/12=-17 | | 4c-9=-5 | | -2/7x | | 2p+15p=34 | | x+3+1=15 | | 206+21x=-82x | | 180=0.5h(11+7) | | 5x+7=8x+-29 | | 10+x=44 | | (88+x)/2=90 | | 2w+4=246 | | X+1=-13 | | -2/7x-4 | | x+2=y+1 | | r^2-1/(2r)-1/2 | | 2(x+2)+58=8x-6(x-5) | | 3x^2+23x-12=0 | | -3+2/7 | | 4a-75=a | | r^2-1/2r-1/2 | | x+40=100 | | z+75=z-7/4 | | g(x)=log(x-6) | | z+7/5=z-7/4 | | 1*2/19=19y | | 88+x/2=90 | | n-46=32 | | 3x-6=-8x+6+7x | | 14=-4(y-3)-3 |